Buddhist Teachings for Improving Mental Health During the COVID-19 Pandemic - Channuwong, Sukhumpong; Ruksat, Suvin (The Journal of Behavioral Science, 2022)
The purpose of this research was to determine how Buddhist teachings can be implemented to improve mental health during the COVID-19 pandemic. A sample of Thai residents (n=356), who practiced Buddhist teachings in the selected Buddhist meditation centers in Bangkok, completed the research questionnaire. Data were analyzed using structural equation modeling (SEM) technique. The research findings revealed that the model had an acceptable fit, chi-square = 127.99, df = 106, p = .07, CMIN/DF = 1.20, GFI = .96, and RMSEA = .02. The results indicated that Buddhist teachings about mindfulness had positive effect on mental health during the COVID-19 pandemic: mindfulness of breathing (β = .95, p = .00), mindfulness of feelings (β = .91, p = .00), mindfulness of the mind (β = .85, p = .00), and mindfulness of the truth of life (β = .75, p = .00). This study contributes to behavioral science by presenting practical ways for Thai people to improve mental health during the COVID-19 pandemic. The findings suggest that Buddhist teachings about mindfulness could be implemented to increase mental happiness, mental peace, mental energy, and mental stability.